INCREASING AGRICULTURAL PRODUCTIVITY IN KEDUNG JAYA VILLAGE, KEDAWUNG SUB-DISTRICT, CIREBON DISTRICT WITH HYDROPONIC TECHNOLOGY - Gian Fitralisma; Winda Dwi Yanthi; Arin Arin; M. Anissul Fata; Winda Dwi Yanthi; Ade Lia; Ade Febry Nur Fitriani; Hasby Nabiel Akmal Ismail (Ann Publisher, 2025)
Abstract: Background. Agriculture is vital for human survival. Therefore, we must continue agriculture and its development. There are several ways we can increase agricultural productivity, one of which is through hydroponics, a method of farming without soil and relying on nutrient solutions as a food source for plants.. Aims. Agriculture is a vital activity for human survival. Therefore, we need to continue agriculture and its development for human survival. Methods. On Tuesday, February 18, 2025, during Real Work Lecture (KKN) activities in Kedung Jaya Village, Kedawung District, Cirebon Regency, a hydroponic farm was visited. The method used was a qualitative approach, intending to understand the impact of the hydroponic system's application. Result. Moreover, in the current situation, the land used for agriculture is decreasing because of the increasing conversion of land, so it is necessary to use a method that takes up less land and is cheap. The emergence of this hydroponic method is to overcome this problem. Conclusion. In this case, the Kedung Jaya Village Government in Kedawung District took the initiative to increase agricultural productivity with this hydroponic method. Implementation. With support from the government and related parties, hydroponics has the potential to become one of the main strategies in achieving sustainable food security in Indonesia